Reading Avicenna in Ayyubid Damascus: The Corrected and Glossated Manuscripts of Faḫr al-Dīn Ibn al-Sāʿātī - Eshera, Osama (Oriens, 2025)
Ibn Abī Uṣaybiʿa’s (d. 668/1270) ʿUyūn al-anbāʾ depicts Ayyubid Damascus as a flourishing intellectual scene where philosophy was regularly studied alongside other sciences, most often medicine. In that context, the court physician and statesman, Faḫr al-Dīn Riḍwān Ibn al-Sāʿātī (d. 618/1221), transcribed and collated dozens of Avicenna’s (d. 428/1037) philosophical works. In doing so, Ibn al-Sāʿātī made a concerted effort to correct scribal errors and textual corruptions that had been introduced in earlier manuscripts. His position in the scholarly networks of the period afforded him access to reliable manuscripts, some of which were Avicenna’s holographs, while others had been transcribed or corrected by Avicenna’s students. Ibn al-Sāʿātī also wrote extensive glosses on the Manṭiq of Avicenna’s Naǧāt. Taken together, Ibn al-Sāʿātī’s codices provide concrete examples of how philosophy was studied and practiced in the Ayyubid context.